THE EFFECTIVENESS COUNSELING MODEL FAMILY PLANNING USING LONG-TERM CONTRACEPTIVE METHODS (LARC) IN UNMET NEED - Nurliana Mansyur; Sri Rahayu Amri; Patmahwati Patmahwati; Ayu Setianingsih; Andi Azzahra Salsabila; Andi Sitti Umrah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
The Family Planning program is one of the focus indicators contained in the SDGs. Indonesia is a country that is facing a high number of unmet needs and low (LARC) coverage, so this problem is outlined in the 2020-2024 Strategic Plan. In fact, the city of Palopo is an area that has a high unmet need (12.05%) while the national target is around 8.6% and (LARC) users are also still relatively low (5.09%). Seeing these conditions, this attention will be focused on family planning services for unmet needs , by providing family planning counseling with several models . Research objective : to analyze the effectiveness of the family planning counseling model on (LARC) users in unmet needs in the city of Palopo. The research method uses pre-experimentation with an intact group comparison approach . The intervention group was given family planning counseling using the Medical Eligibility Criteria for Contraception MEC and audio-visual models, while the control group was the group given family planning counseling using the Decision Making Tools (ABPK) model. This research was carried out in the work area of the Sendana Health Center, Palopo City. The research sample is unmet need. The withdrawal technique uses simple random sampling. The number of respondents in this study was 34 respondents, who were divided into two groups, namely the intervention group and the control group, with 17 people in each group. The research instrument used observation sheets and ABPK, MEC and audio-visual tools. Data analysis using tests chi-square. Research results; There is an effectiveness of the family planning counseling model on the use of (LARC) in unmet needs in Palopo City ( ρ = 0.024 < α value = 0.05), so that there is a need to improve quality family planning services.